PENGARUH PERAN LOCUS OF CONTROL TERHADAP KEPUASAN KERJA PEGAWAI PEMERINTAH DAERAH KABUPATEN MAROS - Muhammad Ikram Idrus (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study aims to examine, analyze and explain the influence of the locus of control factor on job satisfaction of Maros Regency Government Employees. This study examines the causal relationship between locus of control variables on employee job satisfaction, especially in work units within the Maros Regency Government. Withdrawal of research samples based on the proportion of each agency as many as 351 respondents. The research method is included in survey research, and analyzed using Structural Equation Modeling (SEM).The results showed that locus of control had a significant effect on employee job satisfaction. Keywords: Locus of Control, Job Satisfaction